2021
DOI: 10.1186/s40066-021-00301-0
|View full text |Cite
|
Sign up to set email alerts
|

Fortification with mushroom flour (Pleurotus ostreatus (Jacq.) P. Kumm) and substitution of wheat flour by cassava flour in bread-making: Nutritional and technical implications in eastern DR Congo

Abstract: Background The import of wheat flour is the major driver for the high prices and low use of bakery products in non-producing tropical countries such as the Democratic Republic of Congo (DRC). These products’ high prices worsen the risk of malnutrition and food insecurity among rural and resource-poor populations. This study aimed at substituting the imported wheat flour with less expensive local cassava flour fortified with oyster mushroom flour in order to mitigate the nutritional crisis in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Meanwhile, the a * and b * values increased from 6.09 to 8.31 and 26.51 to 27.87, respectively. Irakiza et al 43 also found the same pattern of increase in the a * and b * values and decrease in L * in bread incorporated with MF. Sharma and Gujral 44 also observed the decrease in L * values and increase in a * and b * values with a decrease in BF concentration and vice versa .…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Meanwhile, the a * and b * values increased from 6.09 to 8.31 and 26.51 to 27.87, respectively. Irakiza et al 43 also found the same pattern of increase in the a * and b * values and decrease in L * in bread incorporated with MF. Sharma and Gujral 44 also observed the decrease in L * values and increase in a * and b * values with a decrease in BF concentration and vice versa .…”
Section: Resultsmentioning
confidence: 54%
“…Similarly, Bello et al 27 found that the crude protein content of biscuits increased with the incorporation of mushroom powder. Irakiza et al 43 also observed that the incorporation of MF positively influenced the crude protein content of breads. Gupta et al 41 found that the crude protein content of the cookies increased with decreasing substitution levels of barley and vice versa .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations